2016
DOI: 10.1038/srep34468
|View full text |Cite|
|
Sign up to set email alerts
|

Computer keyboard interaction as an indicator of early Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a slowly progressing neurodegenerative disease with early manifestation of motor signs. Objective measurements of motor signs are of vital importance for diagnosing, monitoring and developing disease modifying therapies, particularly for the early stages of the disease when putative neuroprotective treatments could stop neurodegeneration. Current medical practice has limited tools to routinely monitor PD motor signs with enough frequency and without undue burden for patients and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 37 publications
7
113
1
Order By: Relevance
“…We have previously shown that data collected from an in‐clinic typing task accurately differentiated early PD patients from sex‐ and age‐matched healthy controls, and replicated this result using at‐home, unsupervised data . Recently, we demonstrated similar performance with data acquired during typing on a touch‐screen smartphone .…”
supporting
confidence: 64%
“…We have previously shown that data collected from an in‐clinic typing task accurately differentiated early PD patients from sex‐ and age‐matched healthy controls, and replicated this result using at‐home, unsupervised data . Recently, we demonstrated similar performance with data acquired during typing on a touch‐screen smartphone .…”
supporting
confidence: 64%
“…The latter comply with the findings of other works, such as [6], who introduced a PD motor index related computer-based keyboard interaction. However, in the case of PD, the detection of typing patterns combined with the behavioral change analysis under emotional stimuli may help to identify early onset of PD, in a more holistic and intelligent way.…”
Section: Probing Further Within the I-prognosis Contextsupporting
confidence: 74%
“…Nevertheless, this approach was seldom applied to the medical field, with the rare example of [4], who used the typing speed in login sessions to evaluate sensory-motor speed in healthy subjects [4]. Moreover, Giancardo et al [5], tried to identify a pattern from keystroke dynamics that could detect a state of psychomotor impairment in healthy subjects and the ability to distinguish PD patients at the early stage of the disease from comparable healthy controls [6]. However, none of the previous approaches involved any emotional factors in their studies.…”
Section: Introductionmentioning
confidence: 99%
“…[5]. Subjects in Madrid, Spain performed typing tests by transcribing a folk tale on a word processor for 15 minutes with key stroke data being recorded.…”
Section: Methodsmentioning
confidence: 99%
“…LDA discovers semantically coherent latent topics in a collection of data (called a corpus), with low-level features (or words) being generated from a distribution of topics. Considering a recently released dataset of typing data [5], we present an approach where LDA models are trained on each of the Parkinson's and control groups. We consider a typing session to be analogous to a document, with the key hold durations corresponding to words.…”
Section: Introductionmentioning
confidence: 99%